Does temperature nudging overwhelm aerosol radiative effects in regional integrated climate models?. (April 2017) - He, Jian; Glotfelty, Timothy; Yahya, Khairunnisa; Alapaty, Kiran; Yu, Shaocai
Abstract: Nudging (data assimilation) is used in many regional integrated meteorology-air quality models to reduce biases in simulated climatology. However, in such modeling systems, temperature changes due to nudging could compete with temperature changes induced by radiatively active and hygroscopic short-lived tracers leading to two interesting dilemmas: when nudging is continuously applied, what are the relative sizes of these two radiative forces at regional and local scales? How do these two forces present in the free atmosphere differ from those present at the surface? This work studies these two issues by converting temperature changes due to nudging into pseudo radiative effects (PRE) at the surface (PRE_sfc), in troposphere (PRE_atm), and at the top of atmosphere (PRE_toa), and comparing PRE with the reported aerosol radiative effects (ARE). Results show that the domain-averaged PRE_sfc is smaller than ARE_sfc estimated in previous studies and this work, but could be significantly larger than ARE_sfc at local scales. PRE_atm is also much smaller than ARE_atm. These results indicate that appropriate nudging methodology could be applied to the integrated models to study aerosol radiative effects at continental/regional scales, but it should be treated with caution for local scale applications. Highlights: Temperature changes due to nudging are converted to pseudo radiative effects (PRE). The domain mean PRE is smaller than aerosol effects at surface and in atmosphere. Nudging could be applied to the integrated models to study ARE at regional scales. Integrated models with nudging need be treated with caution to study local scale ARE.